Poverty of Malaysian rice farmers in a changing climate -an empirical investigation in Kedah, Malaysia - Afroz, Rafia (2021)
This research aims to assess the economic impact of climate change on the poverty of rice farmers in Kedah. A personal interview was conducted in a sample of 400 farm households in Kedah, Malaysia. To achieve the goal of the analysis, a logit model was used. The findings indicate that education and non-farm have major positive effect on the probability of being poor for the rice farmers. For Malaysian policymakers, the evidence from this study may be useful in promoting greater preventive measures during the key and off-seasons to counteract climate instability and vulnerability.